Modeling of polarization charge in N-face InGaN/GaN MQW solar cells. (December 2015) - Belghouthi, R.; Taamalli, S.; Echouchene, F.; Mejri, H.; Belmabrouk, H.
Abstract: The present work reports on a theoretical study of spontaneous and piezoelectric polarization effects on the photovoltaic characteristics of InGaN/GaN multiple quantum well solar cells. More especially, it will prove that the use of heterostructures with N-face as a surface polarity can further improve the photovoltaic conversion. A new model including piezoelectric polarization is developed. In this paper, a part of simulation is also paid to analyze the dependence of the photocurrent density, the open circuit voltage, the output power and the efficiency versus the In composition and the number of quantum well units. As has been found, a maximum of energy conversion is expected to achieve 19 percent for optimum alloy composition. An attempt to explain the photovoltaic behavior of the solar cells in correlation of obtained results will be attempted. Highlights: The use of GaN/InGaN MQW with N face configuration enhances the photovoltaic properties. The polarizations charges affect strongly the saturation current and the power density. The polarizations charges do not have a large influence on the Voc .